The Effect of Debt Management, Budgeting Policy, and Green Investment on Financial Growth of Information Technology Companies in West Java - Judijanto, Loso; Supriadi, Adih; Lesmana, Tera (West Science Social and Humanities Studies, 2024)
The study investigates the effect of debt management, budgeting policy, and green investment on the financial growth of information technology companies in West Java. Utilizing a quantitative approach, the research collected data from 190 IT companies using a Likert scale questionnaire (1-5), analyzing the results through Structural Equation Modeling-Partial Least Squares (SEM-PLS 3). The findings highlight the significant impact of effective debt management and sound budgeting policies in promoting financial growth. Additionally, green investment initiatives play a crucial role in enhancing the sustainability and long-term profitability of these companies. The study provides valuable insights for IT companies seeking to balance financial stability and environmental responsibility.